2010
DOI: 10.3390/molecules1512884
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 6-Amino-5-cyano-1,4-disubstituted-2(1H)-Pyrimidinones via Copper-(I)-catalyzed Alkyne-azide ‘Click Chemistry’ and Their Reactivity

Abstract: Abstract:In this paper we present the room temperature synthesis of a novel serie of 1,4-disubstituted-1,2,3-triazoles 4a-l by employing the (3 + 2) cycloaddition reaction of pyrimidinones containing alkyne functions with different model azides in the presence of copper sulphate and sodium ascorbate. To obtain the final triazoles, we also synthesized the major precursors 6-amino-5-cyano-1,4-disubstituted-2(1H)-pyrimidinones 3a-r from ethyl 2,2-dicyanovinylcarbamate derivatives 2a-c and various primary aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The 2(1 H )-pyrimidinones 5a – 5f were synthesized in good yields by the condensation of ethyl 2,2-dicyanovinylcarbamate derivatives 7 with primary aromatic amines ( o -tolylamine or naphthalen-1-ylamine) . Starting from the methyl N -(amino­thio­carbonyl)­imidates 8 and malononitrile, the 2(1 H )-pyrimidinethiones 6a and 6b were obtained in acceptable yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 2(1 H )-pyrimidinones 5a – 5f were synthesized in good yields by the condensation of ethyl 2,2-dicyanovinylcarbamate derivatives 7 with primary aromatic amines ( o -tolylamine or naphthalen-1-ylamine) . Starting from the methyl N -(amino­thio­carbonyl)­imidates 8 and malononitrile, the 2(1 H )-pyrimidinethiones 6a and 6b were obtained in acceptable yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…X-ray crystallographic analyses of N -(1-naphthyl)-2(1 H )-pyrimidinone 5d revealed that the pyrimidinone crystallized in the monoclinic and centrosymmetric space group P 21/ c . Each single crystal of pyrimidinone 5d is composed of both enantiomers (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations